Development of an Embroidery Tutorial Book to Improve Vocational Skills in Grade IX Deaf Children at Karimun State Special Needs School - Asfira, Yuni; Dianasari, Eka Lenggang; Khairiyah, Karunia Yulinda; Meilina, Fitria; Rahmad, Hari Adi (Journal of Nonformal Education and Community Empowerment, 2025)
Development of an Embroidery Tutorial Book to Improve Vocational Skills in Grade IX Deaf Children at Karimun State Special Needs School. Karimun University 2025. This study describes the limitations of deaf children in vocational skills, especially embroidery. This study aims to determine the feasibility and effectiveness of an embroidery tutorial book to improve vocational skills in deaf children at Karimun State Special Needs School. This study uses the RnD (Research and Development) research type with data collection using interviews and questionnaires conducted by a team of media experts, a team of material experts, teacher responses and testing the embroidery tutorial book using pretests and posttests. The type of data produced is qualitative by conducting data analysis in accordance with the assessment criteria guidelines so as to determine the quality of the embroidery tutorial book developed. The results of this study are in the form of an embroidery tutorial book that is used as a guide for deaf children in embroidery vocational skills. Based on the assessment of the media expert team, the average value was 83% with a very valid category, the assessment of the material expert team obtained an average value of 80% with a valid category, the assessment of the teacher's response trial also obtained an average value of 83.5% with a very valid category. While the results of the effectiveness test using the N-gain formula obtained an average increase in value of 0.75% with a high category when viewed from the N-gain interpretation table. It can be concluded that the development of this embroidery tutorial book is declared feasible and effective for improving the vocational abilities of deaf children. This developed tutorial book has a novelty in the form of providing embroidery cloth, namely strimin cloth as a direct implementation in the book. The benefits of this embroidery tutorial book are as a forum or place to hone children's vocational skills, especially in embroidery activities, train children's patience, train children's focus, and train children's fine motor skills.